Zinc Ion-Based Switch-on Fluorescence-Sensing Probes for the Detection of Tetracycline - Yan-Cen Zhan; Jia-Jen Tsai; Yu-Chie Chen (Molecules, 2022)
Tetracycline (TC) is an antibiotic that has been widely used in the animal husbandry. Thus, TC residues may be found in animal products. Developing simple and sensitive methods for rapid screening of TC in complex samples is of great importance. Herein, we demonstrate a fluorescence-sensing method using Zn2+ as sensing probes for the detection of TC. Although TC can emit fluorescence under the excitation of ultraviolet light, its fluorescence is weak because of dynamic intramolecular rotations, leading to the dissipation of excitation energy. With the addition of Zn2+ prepared in tris(hydroxymethyl)amino-methane (Tris), TC can coordinate with Zn2+ in the Zn2+-Tris conjugates to form Tris-Zn2+-TC complexes. Therefore, the intramolecular motions of TC are restricted to reduce nonradiative decay, resulting in the enhancement of TC fluorescence. Aggregation-induced emission effects also play a role in the enhancement of TC fluorescence. Our results show that the linear dynamic range for the detection of TC is 15–300 nM. Moreover, the limit of detection was ~7 nM. The feasibility of using the developed method for determination of the concentration of TC in a complex chicken broth sample is also demonstrated in this work.